Structuring cooperative relationships between organizations - Ring, Peter Smith; van de Ven, Andrew H. (Strategic Management Journal, 1992)
Abstract Alliances and similar cooperative efforts are receiving increased attention in the strategic management literature. These relationships differ in significant ways from those governed by markets or hierarchies, and pose very different issues for researchers and managers. In this paper we address alternative forms of governance in cases where multiple organizations repeatedly cooperate. We explore their characteristics and follow this with a discussion of criteria which we believe bear on the choice of governance: risk and reliance on trust. We offer propositions on relationships between these criteria and the choice of governance mechanisms. In the concluding section of the paper we explore the implications of our analysis for managers and scholars.